Distinct chromosome abnormality patterns for differential diagnosis of hepatocellular carcinoma and cholangiocarcinoma. - Wantakan Ngamsangiam; Sutheemon Techa-Ay; Prakasit Sa-Ngiamwibool; Sasithorn Watcharadetwittaya; Raksawan Deenonpoe; Anchalee Techasen; Natruja Sridakhun; Sureerat Padthaisong; Malinee Thanee (PLoS ONE)
Hepatocellular carcinoma (HCC) and cholangiocarcinoma (CCA) are primary liver cancers with overlapping histopathological features, making accurate diagnosis challenging. This study aimed to identify chromosomal abnormalities that could aid in differentiating these cancers using chromosome microarray analysis (CMA). We analyzed ten frozen tumor tissues each of HCC and CCA, identifying distinct patterns of chromosomal gains and losses. HCC exhibited gains in regions 1p36.32, 1q23.3-q24.1, 3q21.3, 4p16.1, 5q31.1, and 11p15.5, and losses in 2p15, 3p11.1-q11.1, 4q12, 5p12-q11.1, 7q11.23, 14q23.2, 17p11.2, 17p13.3, 22q12.1, 22q12.2-q12.3, and 22q13.2. In contrast, CCA showed gains in 5p13.2, 5p14.1, 8p12-p11.23, 8p22, and 19p13.2, and losses in 1q31.1, 1q42.13, 3p25.3, 6p12.1, 6p25.3, and 17q21.33. Heatmap analysis revealed 17 distinct chromosomal regions between the two groups including 2q14.2, 4p16.3, 5q32, 7p14.3, 7p22.1, 7q11.21, 7q11.23, 7q21.3, 7q22.1, 10q21.3, 18q23, 19p13.2, 19q13.2, 21q21.3, 21q22.13, 22q11.21, and 22q12.2. Among these 1p36.32, 19p13.2, and 19q13.2 emerged as potential biomarkers for differential diagnosis. These findings may aid in confirming cases with overlapping histopathological features contribute to the development of diagnostic tools and improved targeted therapies for HCC and CCA.